الطعن بالتماس إعادة النظر في نظام المرافعات الشرعية السعودي = Appeal By requesting reconsideration of the Saudi Sharia pleading system - Laeba, Muhammad; Alkhulaidi, Maher Hasan; Heriz, Mohammad Salem; Alzayedi, Bander Ali (Faculty of Law, Al-Azhar University, 2020)
للأحكام القضائية حجيتها وحرمت المساس بها، وهذا هو الأصل، إلا أن مبدأ تحقيق العدالة يسمو على حجية الحكم القضائي ولو اكتسب الصفة النهائية، وتتجسد تلك العدالة في مراجعة الأحكام ومن صور مراجعتها الاعتراض عليها سواء بطريق الاعتراض العادي، أو بطريق الاعتراض غير العادي، ومن طرق الاعتراض غير العادية، التماس إعادة النظر، وهو طريق من طرق الاعتراض على الأحكام القضائية غير العادية؛ ذلك أن المنظم السعودي حصر أسباب الاعتراض بهذا الطريق في حالة ما توافر سبب من تلك الأسباب، وقد بين المنظم في نصوص نظام المرافعات الشرعية القواعد والأحكام المتعلقة بهذا الطريق، وفي هذا البحث سنتناول، ماهية التماس إعادة النظر، وطبيعته القانونية، والأحكام التي تقبل الالتماس، وقواعده المنظمة لإجراءات رفعه، وأسباب التماس إعادة النظر، ومن الأهمية بمكان التطرق إلى الأثر القانوني لالتماس إعادة النظر، وقد انتظم في ثلاثة مباحث. **************************************************************************** Judicial rulings have their arguments and prohibited prejudice to them, and this is the basic principle, except that the principle of achieving justice transcends the authenticity of the judicial ruling even if it acquires the final characteristic. Unusual objection, seeking reconsideration is one of the ways to object to extraordinary judicial rulings, because the Saudi legislator has restricted the reasons for objecting to this road in the event that one of those reasons is available, and the legislator has clarified in the provisions of the pleadings system the rules and provisions related to this way, and in this research we will discuss, what is seek reconsideration, it’s legal nature, provisions that accept the reconsideration, the law system rules of procedures for submitting the reconsideration, and the reasons for seeking reconsideration, it is important to address the legal effect of the petition for reconsideration which is explained in six point